Accessibility investigation of semi-volatile organic compounds in indoor dust estimated by multi-ratio equilibrium passive sampling - Rusina, Tatsiana P; Jílková, Simona Rozárka; Melymuk, Lisa; Vrana, Branislav; Smedes, Foppe (Environmental research. Section A, 2023)
Many semi-volatile organic compounds (SVOCs) accumulate in indoor dust, which serves as a repository for those compounds. The presence of SVOCs in indoor environments is of concern because many of them are suspected to have toxic effects. Total SVOC concentrations in the dust are generally used for exposure assessment to indoor contaminants, assuming that 100% of the SVOCs is accessible for human uptake. However, such an assumption may potentially lead to an overestimated risk related to dust exposure. We applied a multi-ratio equilibrium passive sampling (MR-EPS) for estimation of SVOC accessibility in indoor settled dust using silicone passive samplers and three particle size dust fractions, <0.25 mm, 0.25-0.5 mm, and 1-2 mm in dry and wet conditions. Equilibrations were performed at various sampler-dust mass ratios to achieve different degrees of SVOC depletion, allowing the construction of a desorption isotherm. The desorption isotherms provided accessible fractions (FAS), equivalent air concentrations (CAIR), dust-air partition coefficients (KDUST-AIR) and organic carbon-air partition coefficients (KOC-AIR). The highest FAS were observed in the <0.25 mm dust fraction in wet conditions which is relevant for exposure assessment via oral ingestion. The highest CAIR were estimated for several organophosphorus flame retardants (OPFRs), polycyclic aromatic hydrocarbons (PAHs) and synthetic musks. The logKOC-AIR did not differ between dust particle sizes in dry and wet conditions but within compound groups, different relationships with hydrophobicity were observed. Equivalent lipid-based concentrations (CL⇌DUST) calculated using available lipid-silicone partition coefficients (KLIP-SIL) were compared with lipid-based concentrations (CL) measured in human-related samples collected from Europeans. For hexachlorobenzene (HCB), CL⇌DUST, and CL were similar, indicating equilibrium attainment between environment and human samples. Lipid-based concentrations for persistent legacy contaminants were also similar but lower for PBDEs in human samples. Overall, accessibility estimation using MR-EPS in dust further contributes to human risk assessment.
Keywords: Flame Retardants; Environmental Monitoring; retardanty hoření; hodnocení rizik; Lipids; lipidy; lidé; Risk Assessment; prach; Air Pollution, Indoor; znečištění vzduchu ve vnitřním prostředí; těkavé organické sloučeniny; Dust; monitorování životního prostředí; Humans; Volatile Organic Compounds